The Book of Job as sceptical literature - Dell, Katharine 1961- (Berlin New York De Gruyter, 2013)
""CHAPTER 3: A form-critical approach to Job: â€?Parodyâ€? as an overall genre for Job""""a) The deliberate misuse of forms in Job""; ""b) A new overall genre for Job, the parody""; ""CHAPTER 4: The â€?scepticalâ€? setting, content and structure of Job: The scepticism of Job and the author of the book""; ""a) The quest for a context for Job""; ""b) The scepticism of Job as shown in the content of the book""; ""CONCLUSION""; ""Abbreviations""; ""BIBLIOGRAPHY""; ""Indices""
""Table of Contents""; ""INTRODUCTION: â€?Scepticismâ€? as a description of Job""; ""CHAPTER 1: Traditional and critical interpretations of the message of Job: Job the patient or Job the rebel?""; ""Introduction""; ""a) Traditional interpretations of Job""; ""b) Critical interpretations of Job""; ""CHAPTER 2: The quest for an overall classification for Job: Wisdom and genre""; ""a) Job as â€?wisdomâ€? or â€?wisdom literatureâ€?""; ""b) Job as â€?wisdom literatureâ€?""; ""c) The quest for an overall genre for Job""
Includes bibliographical references (pages 220-246) and indexes
Revision of the author's thesis (doctoral)--Oxford University, 1988
Keywords: Bible -- Criticism, interpretation, etc; Bible; Bibel; Skepticism -- Biblical teaching; RELIGION ; Biblical Studies ; Old Testament; RELIGION ; Judaism ; Sacred Writings; Skepticism ; Biblical teaching; Job (bijbelboek); Skeptizismus; Exegese; Formgeschichte; Criticism, interpretation, etc